Dual formation mechanisms of acidic variants in cysteine-engineered antibodies and strategies for their reduction - Zhou, Shasha; Cao, Xinyu; Yin, Xuefei; Xu, Jiawen; Gao, Kai; Wang, Zhenshou (Frontiers in Bioengineering and Biotechnology, 2025)
Cysteine-engineered antibodies (THIOMABs) are pivotal in the site-specific conjugation for ADC therapeutics. In this study, THIOMABs were expressed in CHO cell culture and showed a significantly higher proportion of acidic variants compared to traditional antibodies. A dual formation mechanism for acidic species was identified: glutathione (GSH) capping at engineered cysteine sites and traditional post-translational modifications (PTMs) during cell culture. Moreover, it was found that these two mechanisms exhibited overlapping effects on the formation of acidic species, and their simultaneous elimination was required for significant reduction of acidic variants. Consequently, by modulating temperature and pH to reduce PTMs and supplementing with L-cysteine to displace GSH, the proportion of acidic variants was successfully reduced. This study uncovers dual formation mechanisms of acidic species in THIOMABs and provides a practical cell culture approach, effectively reducing acidic variants and enhancing the quality attributes of THIOMABs.